Measurement of Gross Photosynthesis, Respiration in the Light, and Mesophyll Conductance Using H2 18O Labeling. Issue 1 (27th March 2018) - Gauthier, Paul P. G.; Battle, Mark O.; Griffin, Kevin L.; Bender, Michael L.
Abstract : H2   18 O labeling and IRMS can be used to measure gross photosynthesis, mesophyll conductance, and respiratory uptake in the light in leaflets exposed to 21% and 2% O2 . Abstract: A fundamental challenge in plant physiology is independently determining the rates of gross O2 production by photosynthesis and O2 consumption by respiration, photorespiration, and other processes. Previous studies on isolated chloroplasts or leaves have separately constrained net and gross O2 production (NOP and GOP, respectively) by labeling ambient O2 with 18 O while leaf water was unlabeled. Here, we describe a method to accurately measure GOP and NOP of whole detached leaves in a cuvette as a routine gas-exchange measurement. The petiole is immersed in water enriched to a δ 18 O of ∼9, 000‰, and leaf water is labeled through the transpiration stream. Photosynthesis transfers 18 O from H2 O to O2 . GOP is calculated from the increase in δ 18 O of O2 as air passes through the cuvette. NOP is determined from the increase in O2 /N2 . Both terms are measured by isotope ratio mass spectrometry. CO2 assimilation and other standard gas-exchange parameters also were measured. Reproducible measurements are made on a single leaf for more than 15 h. We used this method to measure the light response curve of NOP and GOP in French bean ( Phaseolus vulgaris ) at 21% and 2% O2 . We then used these data to examine the O2 /CO2 ratio of net photosynthesis, the light response curve of mesophyll conductance, and the apparent inhibition of respiration in the light (Kok effect) at both oxygen levels. The results are discussed in the context of evaluating the technique as a tool to study and understand leaf physiological traits.